Information Culture in Utilizing Digital Libraries for Students of the Faculty of Social and Political Sciences (FISIP) Udayana University - Ginting, Richard Togaranta (Record and Library Journal, 2018)
The purpose of this study was to determine the information culture in usage of digital libraries on students at Faculty of Social and Political Sciences Udayana University and to describe information culture patternson in usage digital library to support academic activities. This research is a descriptive study with qualitative approach. Methods of data collection is done by conducting interviews and literatures studies. The object of this research is the students of the Faculty of Social and Political Science Udayana University. This study gives an overview of the information culture in usage of digital libraries on students atÂ  Faculty of Social and Political Sciences Udayana University. The digital library as an important component in the academic activities of students,thats why this topic is an interesting aspect that deserves to be observed and studied. Behavior and patterns of students in usage of digital library would provide a schematic representation information culture that is inherent in the academic life of students, especially the students of the Faculty of Social and Political Science Udayana University.